Development of Physics Worksheet Based on Higher Order Thinking Skills (HOTS) Integrated with Bilingual Class Learning - Latifah, Sri; Meisuri, Meisuri; Kesuma, Allikha Ade (Indonesian Journal of Science and Mathematics Education, 2023)
The purpose of this research is to create physics worksheets on Higher-Order Thinking Skills (HOTS) Integrated with Bilingual Learning. The method employed was research and development. This research was carried out at MA Diniyah Putri and SMA Global Surya. Non-test instruments in the form of questionnaires and test instruments in the form of questions were used to collect data. The results of the validation of material experts obtained a score of 4.22 with very feasible criteria, and media experts obtained a score of 4.32 with very feasible criteria. The results of the trial in the limited group obtained a score of 3.77 with high criteria and in the field trial a score of 4.45 with excellent criteria. The increase in students' HOTS abilities can be seen after using the worksheet. Therefore HOTS-based physics worksheet integrated with bilingual class learning is feasible to use. It is suggested to further researchers to develop worksheets on different learning materials.